2019
DOI: 10.1016/j.heliyon.2019.e01537
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic cardiac tamponade as a mortal complication of peri-hiatal surgery. Analysis of 30 published cases

Abstract: Iatrogenic cardiac tamponade (ICT) is a dreadful complication of peri-hiatal surgery and vast majority occur during a hernia repair. Strikingly, against all warnings, the incidents and related deaths seem to be increasing. The aim of this review is to provide insight on how to prevent and challenge ICT. PubMed search identified 30 distinct ICTs with 10 deaths (33.3%) due to peri-hiatal procedures. Twenty-nine operations were mechanical repairs and laparoscopic anti-reflux surgery was the primary cause (n:18). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…On a recent review by Çalıkoğlu et al the authors found a 33.3% mortality rate for iatrogenic cardiac tamponade (ICT) [5]; this correlates with previously reported rates varying from 37.5% to 66%, however, there may be higher incidence and mortality rates, as it may be under-reported due to legal implications and lack of diagnosis. In this study, they also reported that mesh placement was responsible for nine out of 10 cases, most of them fixed with tacks; in addition, Köckerling et al revealed that 22 out of 25 reports were secondary to tack fixation [6].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…On a recent review by Çalıkoğlu et al the authors found a 33.3% mortality rate for iatrogenic cardiac tamponade (ICT) [5]; this correlates with previously reported rates varying from 37.5% to 66%, however, there may be higher incidence and mortality rates, as it may be under-reported due to legal implications and lack of diagnosis. In this study, they also reported that mesh placement was responsible for nine out of 10 cases, most of them fixed with tacks; in addition, Köckerling et al revealed that 22 out of 25 reports were secondary to tack fixation [6].…”
Section: Discussionsupporting
confidence: 64%
“…Echocardiography and tomography are efficient diagnostic tools in ICT, as the clinical manifestations might be mistaken with other complications or even with normal recovery after surgery, the use of these diagnostic tests should not be delayed [10]. Regarding treatment, PC is the immediate treatment which can be performed in the ER, although Çalıkoğlu et al reported that open sternotomy was needed in 18 of the 23 patients as a first approach or either as a second procedure [5].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic para-oesophageal hernia repair can be safely performed, by expert practitioners, with mortality rates of 1.3% in elective settings and 8% in emergencies[ 19 , 20 ]. However, major surgical complications can sometimes occur following iatrogenic lesions of the pleura, aorta or pericardium[ 21 ]. In addition, traction on the gastric fundus, the oesophagus-gastric junction and the lower oesophagus can provoke immediate or delayed visceral perforation, with life-threatening consequences[ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Iatrogenic cardiac tamponade (ICT) is a dreadful complication. The reported mortality of cardiac tamponade in peri-hiatal surgery is between 37.5% and 66.6%, [18][19][20] while death due to SVCO may be as infrequent as three in 1000 cases. 21,22 Da Ines et al reported two unusual cases of acute cardiac tamponade following SVC stenting in patients with malignant SVC syndrome.…”
Section: Discussionmentioning
confidence: 99%